Cr3+-doped MgAl2O4 spinel ceramics fabricated by arc plasma melting method; Ceramics International; Vol. 51, iss. 16, Pt. 1 - Valiev D. T. Damir Talgatovich; Shekhovtsov V. V. Valentin Vladimirovich; Sharafeev Sh. M. Sharif Mnirovich; Stepanov S. A. Sergey Aleksandrovich (2025, 2025)
Title screen